When all you have is a dermatoscope-start looking at the nails - Holger A. Haenssle; Andreas Blum; Rainer Hofmann-Wellenhof; Juergen Kreusch; Wilhelm Stolz; Giuseppe Argenziano; Iris Zalaudek; Franziska Brehmer (Mattioli1885, 2014)
Pigmented and non-pigmented nail alterations are a frequent challenge for dermatologists. A profound knowledge of clinical and dermatoscopic features of nail disorders is crucial because a range of differential diagnoses and even potentially life-threatening diseases are possible underlying causes. Nail matrix melanocytes of unaffected individuals are in a dormant state, and, therefore, fingernails and toenails physiologically are non-pigmented. The formation of continuous, longitudinal pigmented streaks (longitudinal melanonychia) may either be caused by a benign activation of matrix melanocytes (e.g., as a result of trauma, inflammation, or adverse drug reactions) or by a true melanocytic proliferation (e.g., in a nevus or melanoma). In general, non-continuous nail alterations, affecting only limited parts of the nail apparatus, are most frequently of non-melanocytic origin. Important and common differential diagnoses in these cases are subungual hemorrhage or onychomycosis. In addition, foreign bodies, bacterial infections, traumatic injuries, or artificial discolorations of the nail unit may less frequently cause non-continuous nail alterations. Many systemic diseases that may also show involvement of the nails (e.g., psoriasis, atopic dermatitis, lichen planus, alopecia areata) tend to induce alterations in numerous if not all nails of the hands and feet. A similar extensive and generalized alteration of nails has been reported after treatment with a number of systemic drugs, especially antibiotics and cytostatics. Benign or malignant neoplasms that may also affect the nail unit include glomus tumor, Bowen's disease, squamous cell carcinoma, and rare collision tumors. This review aims to assist clinicians in correctly evaluating and diagnosing nail disorders with the help of dermatoscopy.